IMUNOGLOBULIN A DI DEMAM BERDARAH DENGUE - Iwan Joseph; Uleng Bahrun; Idham Jaya Ganda; Mansyur Arif (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Recently several serology tests have been used to detect IgM and IgG antidengue, and NS1 antigen. On the last study was launched a new diagnose test using immunochromatography method to detect the specific antidengue IgA antibody. The aim of this study was to evaluate the IgA antidengue performance using immunochromatography method in Dengue Hemorrhagic Fever patients. The study was carried out during March up to July 2010 by a cross sectional method. The samples taken were 1–14 year‘s old patients from the Infectious Tropical Sub Division of the Department of Paediatric, Dr. Wahidin Sudirohusodo Hospital, Makassar. The samples were diagnosed Dengue Hemorrhagic Fever based on the criteria of WHO 1997 and they also subjected to IgM and IgG serology tests as well. The test for IgA is using immunochromatography method. The data was analyzed by Spearman Correlation Test. From the total 40 samples, which consist of 16 (40%) male and 24 women (60%), generally were taken on the fourth day until the sixth day of onset. There were more IgA anti Dengue detected rather than IgM on the secondary infection. The researchers found moderate correlation among the IgA test with IgM (+), IgG (+), or both positive. Based on this study so far it can be concluded that the Dengue IgA test can be used to detect the primary or secondary Dengue virus infection.